The Woodshed mystery - Warner, Gertrude Chandler, 1890-; Cunningham, David (New York, Scholastic, 1962)
The boxcar children uncover a double mystery involving an old friend of Aunt Jane's.
4.5
3-6
Keywords: Mystery and detective stories; Mystery and Detective Stories